Strategies and specific techniques to mass-media relations activities in a public institution - Rus, Mihaela; Tasențe, Tasente; Sandu, Mihaela Luminita; Iscru, Ana Maria (Technium Social Sciences Journal, 2022)
In a democratic society like ours, the role of the press is to gather, to structure and to disseminate accurate and comprehensive information concerning matters of public interest, information that the audience needs. Any coercion or obstruction of these activities, violates the public`s right to information. Freedom of the press also derives from the fundamental freedoms of thought, speech, expression and opinion, enshrined in various national and international laws and normative acts. The concept of the public interest is constantly evolving, which makes it difficult to define it, but, nevertheless, it can be said that it is information of public interest that allows citizens to participate fully in social and political activities. In order to determine what is in the interest of the public, the media and individual journalists will carry out research independently, without any constraints, respecting the job description and the legislation in force.